Entrepreneurship Training and Innovative Pedagogies of Mitigating Perceived Challenges of Business Start-Up Capital to University Graduates - Allan, Issack Shimba (Papers in Education and Development, 2020)
This article presents findings from an experimental research design about entrepreneurship training and innovative pedagogies of mitigating the challenges of university graduates to acquire business start-up capital. The study was motivated by observations that although entrepreneurship training has gained potency in many universities, still many university graduates are not becoming job creators. The experiment involved 800 undergraduate students at the University of Dar es Salaam, from 2016 to 2018, using both quantitative and qualitative data. Findings demonstrate that at the end of the experiment, the innovative pedagogy had positively leveraged the students ' motives to go for self-employment. The findings imply that the use of innovative pedagogies in teaching entrepreneurship can minimise students ' fear of going for self-employment upon graduating. The article contributes in enhancing the theory of innovation, practice of entrepreneurship, jobs creation and informs on policy regarding entrepreneurship training. Keywords: business start-up capital, entrepreneurship training, innovative pedagogies, self-employment, university graduates